Mapping the multidimensional factors of medical student resilience development: a scoping review - Azim, Syeda Rubaba; Yusoff, Muhamad Saiful Bahri; Roslan, Nurhanis Syazni (BioMed Central, 2025)
Resilience plays a vital role in promoting mental wellbeing by facilitating recovery from stressful experiences. Medical students face intense academic and clinical requirements throughout their rigorous training. However, existing literature has predominantly focusing on individual attributes, neglecting the significant role that educational institutions play in resilience development. This scoping review seeks to comprehensively map both individual and institutional factors that contribute to the resilience development among medical students. This scoping review adhered to the Joanna Briggs Institute (JBI) methodology and following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) guidelines. To ensure a rigorous and comprehensive search, multiple databases including Google Scholar, Scopus, PsycINFO, and PubMed were searched for relevant studies published in English between 2000 and Feb 2025, focusing on the resilience or mental health of undergraduate medical students. Two reviewers independently screened the articles, and any discrepancy were resolved through a third reviewer. A descriptive analytical approach and thematic analysis were used to identify key themes in the data. Fifty-nine studies, mostly cross-sectional, were included. Identified themes were broadly categorize into individual factors (e.g., gender, personality traits, personal life events, financial constraints, health-related issues, academic performance) and institutional factors (e.g., academic workload, faculty support and peer interaction, learning environment, extracurricular activities, support systems). This review highlighted that both personal and institutional factors substantially impact medical students’ resilience development. Cultivating a supportive learning environment, strengthening faculty-student relationships, and implementing targeted interventions such as resilience training, mentorship, and increased academic and financial support as well as access to mental health resources can mitigate stressors and enhance students’ resilience. Addressing these multifaceted factors will empower medical students to thrive both personally and professionally, ultimately contributing to the provision of high-quality patient care.